A Sendai Virus-Derived RNA Agonist of RIG-I as a Virus Vaccine Adjuvant - Martínez-Gil, L. (American Society for Microbiology, 2013)
The innate immune system is responsible for recognizing invading pathogens and initiating a protective response. In particular, the retinoic acid-inducible gene 1 protein (RIG-I) participates in the recognition of single- and double-stranded RNA viruses. RIG-I activation leads to the production of an appropriate cytokine and chemokine cocktail that stimulates an antiviral state and drives the adaptive immune system toward an efficient and specific response against the ongoing infection. One of the best-characterized natural RIG-I agonists is the defective interfering (DI) RNA produced by Sendai virus strain Cantell. This 546-nucleotide RNA is a well-known activator of the innate immune system and an extremely potent inducer of type I interferon. We designed an in vitro-transcribed RNA that retains the type I interferon stimulatory properties, and the RIG-I affinity of the Sendai virus produced DI RNA both in vitro and in vivo. This in vitro-synthesized RNA is capable of enhancing the production of anti-influenza virus hemagglutinin (HA)-specific IgG after intramuscular or intranasal coadministration with inactivated H1N1 2009 pandemic vaccine. Furthermore, our adjuvant is equally effective at increasing the efficiency of an influenza A/Puerto Rico/8/34 virus inactivated vaccine as a poly(I·C)- or a squalene-based adjuvant. Our in vitro-transcribed DI RNA represents an excellent tool for the study of RIG-I agonists as vaccine adjuvants and a starting point in the development of such a vaccine.